PERAN PROGRAM MAKAN BERGIZI GRATIS DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 2 GEDOMPOL - Wahyu Nur Cahyanto; Ahmadi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the role of the free nutritious meal program in improving the quality of Islamic Religious Education (PAI) learning at SDN 2 Gedompol. This research employed a qualitative approach with a case study design. The participants consisted of fourth and fifth grade students, Islamic education teachers, and school personnel. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the implementation of the free nutritious meal program contributes to enhancing students’ learning readiness and concentration during PAI lessons. In addition, the program supports the internalization of Islamic values such as gratitude, discipline, cooperation, and proper eating manners. The learning environment also becomes more conducive, which positively influences the teaching and learning process. Therefore, the program not only addresses students’ nutritional needs but also plays a significant role in supporting the quality of PAI learning in elementary school settings.